EFEKTIVITAS PEMBERIAN ZPT GIBERELIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAYAM MERAH (Amaranthus tricolor L.) VARIETAS MIRA - Harianja, Benny; Hayatul Rahmi; Yayu Sri Rahayu (Jurnal Agrotech, 2024)
Red spinach is one of the horticultural plants with numerous benefits. This research aims to determine the most effective concentration of the plant growth regulator gibberellin on the growth and yield of red spinach (Amaranthus tricolor L.). The study was conducted in the Experimental Field PERURI in Sirnabaya Village, East Teluk Jambe District, Karawang Regency, from June to October. The research method employed was an experimental approach using a randomized complete block design (RCBD) with a single factor consisting of 5 treatments and 5 replications, namely A (0 ppm), B (50 ppm), C (100 ppm), D (150 ppm), and E (200 ppm). The research results indicate that gibberellin application significantly influences plant height at 14, 21, and 28 days after planting, leaf count at 7 days after planting, leaf area, fresh weight per plant, and fresh weight per plot. Treatment D (150 ppm) yielded the best results for plant height up to 28 days after planting at 22.73 cm, leaf count up to 28 days after planting at 19.60 leaves, fresh weight per plant at 30.42 g, and weight per plot at 912.68 g.